MAIN DIRECTIONS OF THE DEVELOPMENT OF THE LIVESTOCK NETWORK IN THE REPUBLIC OF UZBEKISTAN (Proceedings of International Educators Conference, 2024)
In the article, priority directions for the development of agriculture, in particular, livestock industry in the Republic of Uzbekistan in recent years, legal documents and their essence, economic geographical factors affecting the development of the industry, and the development of the industry are proposed. and recommendations are given.